Variational Uneven Illumination Correction with Double-norm Hybrid Constraints for Remote Sensing Imagery - LI Shuo (Acta Geodaetica et Cartographica Sinica, 2018)
In response to the uneven illumination of remote sensing image, a variational method of uneven illumination correction with double-norm hybrid constraints is proposed. Firstly, the deficiency of the variational method with single norm constraint is analyzed. A new variational model is constructed according to the characteristics of the reflectance image and the illumination image. The L1 norm and the L2 norm are adopted to constraint the texture and detail of reflectance image and the smoothness of the illumination image, respectively. Then, the solution of the variational model is translated into three sub-problems with split Bregman method and calculated using alternate iteration method to accelerate the computation. The mean of the illumination image enhanced with Gamma correction method is multiplied by the reflectance image. Finally, the contrast stretch transformation is implemented for a better performance. Experimental results indicate that the proposed method is practical and feasible. Compared with the variational Retinex method with single norm constraint, the proposed method performs better in correcting the uneven illumination and preserving the textures and details of the remote sensing image. In addition, the proposed method is more efficient, of which the running time is less than one seventh of that of the variational Retinex method with single norm constraint.